Comparative Evaluation of Infectious Potential, Resistance Patterns and Key Determinants of Escherichia coli in Urinary Tract Infection: A Cross-sectional Study - Kushani Bhaine; Dhara Patel; Artee Tyagi (Journal of Clinical and Diagnostic Research)
Introduction: The emergence of Multidrug-Resistant (MDR) Escherichia coli (E. coli) and its opportunistic uropathogenicity complicates the treatment of Urinary Tract Infections (UTIs), consequently increasing healthcare costs and mortality rates. Uropathogenic E. coli (UPEC) is the primary cause of most UTIs, such as cystitis and pyelonephritis. These infections can lead to severe complications, including acute renal failure, affecting both healthy individuals and renal transplant patients. Aim: To scrutinise the infectious prevalence of E. coli and the occurrence of UPEC, with relative proportional scrutiny of the resistance spectrum and determinants associated with UTIs to identify their management strategies. Materials and Methods: This cross-sectional study was conducted between February 2019 and February 2023 at the Microbiology Laboratory of Charotar Hospital and Research Foundation (CHRF), Anand, Gujarat, India. A total of 461 clinical specimens, including 153 urine samples, were processed to determine the infectious magnitude of E. coli and the rate of UPEC. Their resistance spectrum and mechanisms were compared using disc diffusion assays and statistically analysed by Chi-square value, two-tailed p-value, odds ratios (ORs) and confidence intervals using Microsoft Excel 2021 and CDC Epi Info™ software by the US Department of Health and Human Services, Centres for Disease Control and Prevention. Results: E. coli was predominant in UTIs, comprising 45% of UPECs. Of the E. coli samples, 62.9% were Extended Spectrum Beta-Lactamase (ESBL) producers, showing complete resistance to penicillins and cephalosporins. Furthermore, ESBL UPEC demonstrated a high level of resistance to carbapenems and fluoroquinolones, but exhibited good sensitivity to Nitrofurantoin (100%) and Fosfomycin (75%). Additionally, 33.3% of E. coli were carbapenem-resistant, with 14.8% found to produce Metallo-Beta-Lactamase (MBL). Hospitalisation in the past year was identified as a significant associated risk factor (p-value <0.05). Conclusion: Nitrofurantoin and Fosfomycin are significant drugs for the empirical management of UTI cases. However, for effective management of Antimicrobial Resistance (AMR), definitive therapy must be continued in a synergistic combination after ensuring regular culture and sensitivity practices. The increasing rate of carbapenem resistance, limited therapeutic options for ESBL and the constrained results of carbapenemase phenotypes necessitate the identification of the precise causes by molecular assay for effective clinical guidance.